Exploring Customer Loyalty in the Department Store Retail Setting: A Comprehensive Study of ABC Shopping Mall - Xinran, Wang; Wisedsind, Noppawan; Ruanggoon, Jirapong (Science, Technology, and Social Sciences Procedia, 2024)
The objectives of this research were: 1) to investigate the customer loyalty of ABC shopping mall after the COVID-19 pandemic; 2) to analyze the factors that affected customer loyalty with ABC shopping mall, and; 3) to find out the business strategies that could improve the competitiveness and customer loyalty of ABC shopping mall. This study adopted a mixed methods research approach, with data collected through questionnaire surveys and interviews. Quantitative data were analyzed using descriptive statistics, correlation analysis, and linear regression, while qualitative data were analyzed using thematic analysis. The findings showed that: 1) there were varying levels of customer loyalty at ABC Shopping Mall after COVID-19. While trust in safety measures was high, challenges persisted in service quality, store ambiance, and value perception. Issues such as long queues, cleanliness, and pricing disparities compared to online options needed addressing; 2) the regression analysis revealed that product quality, service quality, store atmosphere, convenience, perceived value, and customer satisfaction collectively accounted for 93.6 % of the variation in customer loyalty towards ABC Shopping Mall. All identified factors demonstrated a significant positive influence on customer loyalty, and; 3) to enhance customer loyalty, ABC Shopping Mall could implement strategies such as relationship marketing, differentiated store atmosphere management, adjusted pricing strategies, and establishing a specialized customer relationship management (CRM) team. These efforts aimed to personalize services, cater to diverse demographics, offer competitive pricing, and proactively addressed customer needs, ultimately fostering stronger connections and sustained success for the mall.